Letter from the Editor - Rigoberto Castillo (Asociación Colombiana de Profesores de Ingles, 2016)
This HOW Journal issue number 12 collects papers that the Editorial Committee and the Editorial Advisory Board felt were of high quality. There were difficulties in receiving enough contributions on time to put the issue together. It was originally planned for the first semester of 2006, but it comes to light in October on the occasion of the 41st ASOCOPI Conference.